Footwear‐centric body area network with directional UWB antenna. Issue 14 (1st July 2013) - Gaetano, D.; Sipal, V.; McEvoy, P.; Ammann, M.J.; Brannigan, C.; Keating, L.; Horgan, F.
Abstract : A footwear‐centric body area network employing a directional antenna is compared with waist‐centric systems using omnidirectional and directional antennas. The effect of body movements on path gain is analysed for two bands at 3.99 and 7.99 GHz. The path gain and data rate results demonstrate that footwear‐centric configurations are equivalent to or better than waist‐centric body area networks.